2022
DOI: 10.1016/j.ajo.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Disc Hemorrhages Are Associated With Localized Three-Dimensional Neuroretinal Rim Thickness Progression in Open-Angle Glaucoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
2
1
0
1
Order By: Relevance
“…In accordance with previous studies, 23–28 the presence of ODH was revealed as a clinical factor associated with rapid RNFL thinning in the current study. In our Cox proportional hazard model, thinner CCT was also a risk factor for RNFL progression (Table 3), which is also in agreement with those of numerous authors that eyes with glaucoma progression have significantly thinner CCT 29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies, 23–28 the presence of ODH was revealed as a clinical factor associated with rapid RNFL thinning in the current study. In our Cox proportional hazard model, thinner CCT was also a risk factor for RNFL progression (Table 3), which is also in agreement with those of numerous authors that eyes with glaucoma progression have significantly thinner CCT 29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…The no-DH group might have included patients with undetected DHs, considering the short duration of DH [ 39 ]. However, the interval of three months for DH observation in this study is comparable to that adopted in other studies on DHs [ 11 , 14 , 15 , 16 , 17 , 18 , 20 , 22 , 24 , 29 , 32 , 33 , 34 , 36 , 37 , 38 ]. Although we did not examine the association between DH and systemic diseases or drug usage, systemic hypertension [ 19 , 21 ], diabetes [ 19 , 45 ] and use of aspirin [ 45 ] were reported to be significantly associated with DH occurrence.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding structural progression, photographic enlargement of retinal nerve fiber layer (RNFL) defects is closely associated with DH [ 9 ]. Recently, studies using OCT reported faster thinning of the circumpapillary RNFL, neuroretinal rim, macular retinal ganglion cell (RGC), plus the inner plexiform layer (GCIPL), a representative thickness parameter of the macular inner retinal layers, in association with the occurrence of DH at the site of structural changes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Геморрагии по краю ДЗН являются значимым симптомом ГНД. Давно доказано, что геморрагии ДЗН сопряжены с более быстрой потерей полей зрения и более выраженным истончением слоя нервных волокон сетчатки и ганглиозного комплекса сетчатки по данным ОКТ, а также истончением нейроретинального ободка [54][55][56][57].…”
Section: геморрагии на дзн как симптом глаукомы нормального давленияunclassified